Features of the Termination of Employment Relations Under the Conditions of Marital State in Ukraine - Khmara, Mila (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
The article deals with the peculiarities of the termination of labour relations in the conditions of martial law in Ukraine.The war, the imposition of martial law, the mobilization of workers, temporary occupation, and the destruction of various enterprises in Ukraine affected the activities of all subjects of economic activity, institutions and organizations throughout the territory of our country and led to changes in the legal regulation of various spheres of the state’s life, including including labour relations. With the adoption of the Law of Ukraine of 15.03.2022 № 2136-IX “on Organization of labour relations in the conditions of military condition” in Ukraine certain peculiarities of passing of civil service and service in local self-government bodies, peculiarities of labour relations of employees of economic entities are defined. This law introduced significant changes to labour legislation, including changes to the termination of labour laws and labour contracts.The current state of legal regulation of termination of labour relations is outlined.The two types of termination of the labour contract, which are valid during the military condition, are analyzed: the complete termination of the labour contract and suspension of the employment contract, which can be initiated by both the employee and the employer.It is noted that the suspension of the employment contract is a new effective legislation, the essence of which is to temporarily stop the employer providing the employee with work and temporarily stop the employee performing work under the concluded labour contract in connection with the armed aggression against Ukraine, which excludes the possibility of both parties of labour relations to fulfill the obligations stipulated by the labour contract.It is noted that the introduction of certain restrictions on the rights of employees of economic entities, as well as enterprises, institutions, organizations, regardless of the form of ownership, are justified, as they are aimed at the most efficient organization of work during the war, but in some cases lead to the violation of the rights of employees.